2020
DOI: 10.21203/rs.3.rs-76169/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with the mental health of adolescent university students during COVID-19 quarantine in Japan

Abstract: Background: University students in Japan have been quarantined during the current COVID-19 pandemic. The resulting social avoidance may increase students’ anxiety about the pandemic and adversely affect their mental health. To obtain basic data for a university health policy, we investigated factors associated with the mental health status of 570 students of a national university in Japan during quarantine. Methods: Participants completed an online questionnaire assessing respondent characteristics (gender, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A third finding of the study was that higher SOC was associated with less psychological distress, that is, lower anxiety, depression, and hopelessness. This finding is supported by several studies (Gómez-Salgado et al, 2020; Hirano et al, 2020; Schäfer et al, 2020) conducted during the COVID-19 pandemic that suggest that individuals high in SOC experience fewer adverse psychological symptoms and cope more effectively with distress compared with those with low SOC. High SOC has been associated with improved health status, greater work engaged, and fewer family and work-related conflicts (Gómez-Salgado et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A third finding of the study was that higher SOC was associated with less psychological distress, that is, lower anxiety, depression, and hopelessness. This finding is supported by several studies (Gómez-Salgado et al, 2020; Hirano et al, 2020; Schäfer et al, 2020) conducted during the COVID-19 pandemic that suggest that individuals high in SOC experience fewer adverse psychological symptoms and cope more effectively with distress compared with those with low SOC. High SOC has been associated with improved health status, greater work engaged, and fewer family and work-related conflicts (Gómez-Salgado et al, 2020).…”
Section: Discussionsupporting
confidence: 61%
“…According to Antonovsky (1993), SOC affects how individuals perceive life stressors and influences their appraisals of the extent to which they can cope with adverse circumstances. Individuals with high SOC tend to use task-oriented problem-solving approaches and positive reframing to cope with stress (Hirano et al, 2020). It is probable that young adults in the sample with high SOC are able to appraise pandemic-related restrictions as time-limited, aimed at promoting their safety, and an opportunity to spend more time with loved ones and deepen these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by studies carried out in China, Italy, Spain, and Japan. 36,[38][39][40][41] In the current study, as the duration of quarantine increased by one unit, depression among quarantined individuals increases by 1.3. This might be due to individuals being unable to adapt to a new environment and prolonged periods of loneliness.…”
Section: Discussionmentioning
confidence: 51%
“…Overall, studies indicating moderating effects of SOC during the COVID-19 pandemic often had small effect sizes and findings were inconsistent with effects differing for genders (Hirano et al, 2020) or contrasting directions of the interaction (Barni et al, 2020). Therefore, based on the available studies, a buffering effect of SOC for mental health impacts of the COVID-19 crisis cannot be verified.…”
Section: Soc During the Covid-19 Crisismentioning
confidence: 96%
“…They additionally observed the reverse moderating effect of SOC for the association of fear of infection with wellbeing: People with stronger SOC reported lower wellbeing when they feared a COVID-19 infection but the effect was less pronounced in people with weaker SOC. In a preprint, Hirano et al (2020) surveyed 570 university students (59% women) and reported a moderating effect of SOC in male Japanese students, but not in female students. Male students with anxiety of COVID-19 reported fewer mental health impairments when their SOC score was higher, supporting a buffering effect in men only.…”
Section: Introductionmentioning
confidence: 99%